Navigating Diabetes in Pregnancy: Critical Approaches to Mitigate Risks and Improve Outcomes for Mother and Child - Zoe Paige Garvey; Abhishek Gupta; Nicole Taylor; Mahesh Thirunavukkarasu; Nilanjana Maulik (Metabolites)
With the increasing prevalence of diabetes and its growing impact on maternal and fetal health, management during pregnancy has become critical. This review describes the pathophysiology of insulin resistance during pregnancy, adverse outcomes correlated with diabetic pregnancies, and current management strategies. We investigate two leading approaches to managing pregnant patients with diabetes—lifestyle intervention and drug treatment. Lifestyle intervention, including dietary counseling, exercise regimens, patient education, and self-administered blood glucose monitoring, has demonstrated promising results in the management and prevention of gestational diabetes mellitus (GDM). Early intervention and treatment of at-risk patients have been critical for positive outcomes. Drug treatment, focusing on the utilization of insulin, insulin analogs, and antihyperglycemic agents has shown efficacy in achieving glycemic control and improving maternal and neonatal outcomes. These findings indicate that a combination of early lifestyle intervention and targeted drug treatment yields the most benefit in managing diabetes in pregnancy. To augment treatment, continuous glucose monitoring and telemedicine have become valuable tools in managing diabetes during pregnancy. Future research should aim to develop more effective antihyperglycemic agents, improve telehealth accessibility, and enhance preconception care for women at risk of developing GDM. By addressing these areas, we can significantly reduce the adverse outcomes associated with diabetes in pregnancy and improve overall maternal and fetal health.